Sequential Treatment of Biliary Atresia With Kasai Hepatoportoenterostomy and Liver Transplantation: Benefits, Risks, and Outcome in 393 Children - Tambucci, Roberto; de Magnée, Catherine; Szabo, Margot; Channaoui, Aniss; Pire, Aurore; de Meester de Betzenbroeck, Vanessa; Scheers, Isabelle; Stephenne, Xavier; Smets, Françoise; Sokal, Etienne M.; Reding, Raymond (Frontiers in Pediatrics, 2021)
Introduction: Surgical treatment of biliary atresia (BA) is still based on sequential strategy with Kasai hepatoportoenterostomy (KP) followed by liver transplantation (LT), in case of complicated secondary biliary cirrhosis. Concerns have been expressed regarding the risks of LT related to previous KP, suggesting primary LT as an exclusive treatment of BA. Methods: Single-center retrospective analysis including 393 pediatric patients undergone LT for BA from 1993 to 2018, categorized into two groups: with (KP) or without (NoKP) previous KP. Pre-LT clinical condition was estimated considering age at LT, time on waiting list, pediatric end-stage liver disease score (PELD), and presence of portal vein hypoplasia. Post-LT outcome was evaluated considering patient and graft survival rates, and need for early reoperation due to abdominal or graft-related complications (<45 days after LT). Results: Two-hundred-ninety-six patients (75.3%) were categorized in KP, and 97 (24.7%) in NoKP group. Median age at LT was 1.14 in KP and 0.85 years in NoKP groups (p<0.0001). PELD score was significantly less severe in KP patients (p<0.05). One-year patient survival rate was 96.9% and 96.8% in KP and NoKP groups, respectively (p=0.4255), and the corresponding graft survival was 92.5% and 94.8% (p=0.9712). The need for early reoperation was more frequent in KP group (29.8%) vs NoKP group (12.4%, p=0.0120). The rate of bowel perforation was non significantly higher in KP group (8.1%) vs NoKP group (3.1%, p=0.1070). Conclusions: The sequential strategy including KP and LT allowed performing LT in patients with significant older age and better clinical conditions, when compared to those transplanted without previous KP. Patient and graft survivals were not impacted by previous KP. Although previous KP was associated with an increased rate of post-LT surgical complications, bowel perforation and bleeding did not occur significantly more frequently. Such results support the current strategy based on sequential treatment.